A disposable biosensor for urea determination in blood based on an ammonium-sensitive transducer - Eggenstein, Claudia; Borchardt, Michael; Diekmann, Christoph; Bernd Gründig; Dumschat, Christa; Cammann, Karl; Knoll, Meinhard; Friedrich Spener (Biosensors & bioelectronics, 1999)
A potentiometric urea-sensitive biosensor using a NH + 4-sensitive disposable electrode in double matrix membrane (DMM) technology as transducer is described. The ion-sensitive polymer matrix membrane was formed in the presence of an additional electrochemical inert filter paper matrix to improve the reproducibility in sensor production. The electrodes were prepared from one-side silver-coated filter paper, which is encapsulated for insulation by a heat-sealing film. A defined volume of the NH + 4-sensitive polymer matrix membrane cocktail was deposited on this filter paper. To obtain the urea-biosensor a layer of urease was cast onto the ion-sensitive membrane. Poly (carbamoylsulfonate) hydrogel, produced from a hydrophilic polyurethane prepolymer blocked with bisulfite, served as immobilisation material. The disposable urea-sensitive electrode was combined with a disposable Ag/AgCl reference electrode to obtain the disposable urea biosensor. The sensor responded rapidly and in a stable manner to changes in urea concentrations between 7.2×10 −5 and 2.1×10 −2 mol/l. The detection limit was 2×10 −5 mol/l urea and the slope in the linear range 52 mV/decade. By taking into consideration the influence of the interfering K +- and Na +- ions the sensor can be used for the determination of urea in human blood and serum samples (diluted or undiluted). A good correlation was found with the data obtained by the spectrophotometric routine method.